Study on HR policies and practices with reference to Excel Engineering and Equipments, Coimbatore - SARASU, Dr A.; S, INDRA PRASANTH; A, ARUL CYRIL CHINNAPPAN; R, V. SANJEEV PRASATH; M, GOKUL PRAKASH (The journal of contemporary issues in business and government, 2021)
Human resource policies are continuing guidelines on the approach the organization intends to adopt in managing its people. It represents specific guidelines to HR managers various matters concerning employments. It states that intend of the organization about different aspects of Human Resource management such as recruitment, promotion, compensation, training, selections etc. They define the conception and value of the organization on how people and things should be treated. Therefore, it serves as a reference point when human resources management practices are being developed or when decisions are being made about people. A good HR policy could provide generalized guidance on the approach adopted by the organization, and therefore its employees, concerning various aspects of employments. A procedure spells out precisely what action should be taken in line with the policy. The main objective of the study is to understand the problem and to analyze the perception of employees on HR practices implemented. For this purpose a sample of 124 was collected from respondents were percentage analysis, descriptive statistics and Kruskall Wallis test and one-way ANOVA were used as tools to analyze the data and the conclusion is that Evaluation and periodic assessment are important for improvement and effectiveness.